2018
DOI: 10.5267/j.ac.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of orthogonal arrays and design of experiment via Taguchi L9 method in probability of default

Abstract: The Taguchi's orthogonal array is based on a mathematical model of factorial designs. This paper investigates the effects of four parameters in Probability of Default (PD) using BlackScholes model (BSM) for call option at one period by considering asset value , firm's debt , expected growth and the volatility . The main aim is to determine which parameters affect mostly on PD of a firm. The experiment is based on the orthogonal array L9 in which the four parameters are varied at three levels. Finally, the ANOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Note: "The normal plot of the residuals is used in order to verify the assumption that it follows the normal distribution. It was found that the residuals approximately follow straight line" (Dar and Anuradha, 2018).…”
Section: Result Analysis and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Note: "The normal plot of the residuals is used in order to verify the assumption that it follows the normal distribution. It was found that the residuals approximately follow straight line" (Dar and Anuradha, 2018).…”
Section: Result Analysis and Discussionmentioning
confidence: 95%
“…The parameters that were used in this study are catalyst loading, type of catalyst, nitrogen gas flow rate and catalyst loading. Dar and Anuradha (2018) used Taguchi orthogonal L9 array, ANOM and ANOVA in order to identify which parameter affects more on PD. It was shown that the volatility affects more on PD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the basis of range analysis of the weight gain for Populus tomentosa treated by steaming, Table 13 [16]. The range value of steaming time (2.094) was higher than those of steaming temperature (1.782) and moisture content (1.782), this result indicated that the steaming time had the greatest contribution to the weight gain, followed by steaming temperature and moisture content.…”
Section: Resultsmentioning
confidence: 96%
“…The DOE with Taguchi orthogonal array needs good preparation, intelligent experiment structure, and specialist result interpretation. The Taguchi method became the traditional DOE method [13,14]. It was designed by Dr. Genechi Taguchi (1940 by the Japanese engineer) and came to be known as one of the best plays for scientists and engineers [15].…”
Section: Taguchi Methodsmentioning
confidence: 99%